Mengkabong, North Borneo in the eighteenth century - Yusry Sulaiman; Mosli Tarsat; Rizal Zamani Idris; Mohd Firdaus Abdullah (Universiti Pendidikan Sultan Idris, 2023)
This article aims to offer a glimpse into Mengkabong's history in the eighteenth century. The goal is to focus on the history of Mengkabong through anecdotes obtained from the natives. Mengkabong is historically notable since it served as the major naval base during the reign of Sultan Omar Ali Saifudin I. Furthermore, the discussions offer some light on two major groups of people in Mengkabong (Dusun Lotud and Bajau) as well as Raja Tua's role. During the eighteenth century, the title Raja Tua referred to the representative of the Sultanates of Brunei who held the highest administrative position in Mengkabong. Apart from the military, he was also in charge of the administration and welfare of the society. The data collected was from the primary and secondary sources. The discussions presented here are also based on fieldwork at derelict tombs and ancient forts in Mengkabong, as well as oral history and interviews. The study is essential in understanding North Borneo's early history before the arrival of western powers. Finally, this article provides some insight into the history of Mengkabong in the early history of Sabah.